Hubungan Faktor Internal dan Faktor Eksternal denganMotivasi Konsultasi Gizi pada Pasien Hipertensi di Poliklinik Gizi RSUD Dr.Moewardi - Nugraheni, Nurul Astri, Siti Zulaekah, A., M.Si, dr. Annita Kern, M.Si (2013)
Background. Hypertension is often called the silent killer because it can cause sudden death. DASH (Dietary Approaches to Stop Hypertension) diet and counseling play a role in lowering blood pressure on pre-hypertension subjects. The motivation will affect patients to visit nutritional clinic for consultation. Objective. This aim of this research was to determine the correlation between internal and external factors and nutrition consultation motivation on hypertension patient in nutrition clinic Dr. Moewardi Hospital. Research Method. Type of this research was observasional research with cross-sectional approach. Subjects were obtained using consecutive sampling with total subjects were 32. Correlation test using Fisher Exact Test and Chi-Square. Result. The results showed that subjects with elderly age (71,9%) and good knowledge (75,0%), completed high school education (65,63%), good family support (59,4%) and support good health (65,6%). There was not any significant correlation between age and education with nutrition consultation motivation with p value of each is 0,235 and 1,0. There was significant correlation between knowledge, family support and medics support and nutrition consultation motivation to nutrition clinic Dr. Moewardi Hospital with p value of each is 0,01; 0,016; and 0,027. Conclusion. Internal factor that have correlation with nutrition consultation motivation was level of knowledge. External factors that have correlation with nutrition consultation motivation were family and medics support.